Thyroid dysfunction induced by amiodarone in clinical practice - Paz-Ibarra, José Luis (2011)
Amiodarone is a potent class III anti-arrhythmic drug used in clinical practice for the prophylaxis and treatment of many cardiac rhythm disturbances, ranging from paroxismal atrial fibrillation to life threatening ventricular tachyarrhythmias. Amiodarone often causes changes in thyroid function tests mainly related to inhibition of 5'-deiodinase activity resulting in decrease in the generation of T3 from T4 with consequent increase in rT3 production and decrease in its clearance. In 14-18% of amiodarone-treated patients, there is overt thyroid dysfunction, either amiodarone-induced thyrotoxicosis (AIT) or amiodarone-induced hypothyroidism (AIH). Both AIT and AIH may develop either in apparently normal thyroid glands or in glands with preexisting clinically silent abnormalities. AIT is primarily related to excess iodine-induced thyroid hormone synthesis in an abnormal thyroid gland (type I AIT) or to amiodarone-related destructive thyroiditis (type II AIT). AIH pathogenesis is related to escape failure from the acute Wolff-Chaikoff effect due to defects in thyroid hormonogenesis or, in patients with positive thyroid autoantibody test, to concomitant Hashimoto's thyroiditis. AIT is more common in iodine-deficient regions of the world, whereas AIH is usually seen in iodine-sufficient areas. In contrast to AIH, AIT is a condition difficult to diagnose and treat, and discontinuation of amiodarone is usually recommended. In this review discusses, according to data from current literature, alterations in thyroid laboratory tests seen in euthyroid patients under treatment with amiodarone and the epidemiology and treatment options available of amiodarone-induced thyroid dysfunctions (AIT and AIH).